Towards a re-assessment of the Ancient North Arabian alphabets used in the oasis of al-ΚUlā - Macdonald, Michael C.A. (Proceedings of the Seminar for Arabian Studies, 2018)
It has so far proved impossible to assign absolute dates to any of the pre-Islamic monuments in the oasis of al-ΚUlā. Frustration at this has driven some scholars to try to establish a sequence of letter forms in the inscriptions as a means of dating. This enterprise was doomed to failure, however, since such a sequence could be no more than subjective and hypothetical if it was not itself based on dated documents. This paper tries to clear up some of the misconceptions which have plagued the subject for decades, and concentrates on research questions which the material, as it exists at present, is capable of answering, leaving the problem of chronology until archaeological and historical research in the oasis has provided sufficient dating evidence.